MODELING TUTUPAN LAHAN di DAS TIKALA BERDASARKAN KAPASITAS SALURAN SUNGAI TIKALA - Telah, Heinsy A.J.; Rombang, J. A.; Walangitan, H. D. (Universitas Sam Ratulangi, 2018)
ABSTRACTÂ Tikala river is the main channel of Tikala watershed. Tikala watershed covers an area of 9215,89 kmÂ² and the length of the main river is 23,73 km. The decline in Tikala watershed quality is marked by high fluctuations of river debit, the increase of erosion and sedimentation rates, and destructive flood. Comparing to floods caused by other rivers in Manado city, flood caused by Tikala river on the 15th January 2014 was the worst case. For this reason, research was conducted to analyze the capacity of river channels in three sampling spots, chosen through purposive sampling methods, and to model types of landuse suitable to the capacity of river channels. Results of river channel capacity analysis at 3 sampling spots using Manning's equation were 45,29 m3/s, 131,58 m3/s, and 36,39 m3/s. Five models of landuse were carried out for Tikala Watershed and the most suitable landuse model is the 4th type in which open area, dry agriculture, and 4.099 ha of dry agriculture mixed with shrubs were converted into an agroforestry system.Keywords: watershed, river capacity, modeling